(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
With the need to accelerate the marine renewable energy technology development pathway, and progress technology development through the TRL’s to commercial acceptance in a timely manner, a key component in this is the provision of skilled personnel to inform technology development and evolution, and provide access to ‘fit-for-purpose’ infrastructure to provide system/ sub-system engineering evaluation; and the provision of robust empirical data upon which informed decision making on technology up-scaling and commercialisation is made. MARINERG-i_PP galvanises Europe’s marine renewables research infrastructures to form a European Research Infrastructure Consortium (ERIC) which will produce the scientific, business and implementation plan for an integrated European Research Infrastructure, designed to facilitate the future growth and development of the Offshore Renewable Energy sector. It is a key step in forming an independent legal entity of distributed testing infrastructures, united to create an integrated centre for delivering Offshore Renewable Energy. By consolidating expertise, investment and access to infrastructures, the MARINERG-i Research Infrastructure will foster innovation across a variety of Offshore Renewable Energy technologies and stages of development. As the only integrated Offshore Renewable Energy platform of this scale worldwide, it will be the epicentre of this developing industry. The MARINERG-I mission is to deliver: Technical de-risking and increasing investor confidence through the development and implementation of best practices; quality metrics; standards Leverage existing local knowledge and capabilities to accelerate the development of the Offshore Renewable Energy industry. Informing national and EU policy and investment strategies to capitalise on leadership in the Offshore Renewable Energy sector. This paper will be the first reporting of the program of work being undertaken and the initial outputs/ deliverables and the implementation of these to demonstrate the initial impact of the MARINERG-I ERIC.